Cardiac arrhythmia in a professional football player - Krome, C. N.; Tucker, A. M. (The Physician and Sportsmedicine, 2003)
The use of over-the-counter dietary supplements has risen dramatically, and adverse events can be severe. Physicians should recognize the dangers that ephedrine-containing supplements present and remain vigilant for sympathomimetic symptoms in young, otherwise healthy, patients. This case illustrates how the use of a popular weight-loss supplement by a 27-year-old professional football player apparently resulted in cardiac arrhythmia requiring direct cardioversion.